Impact of the Quality of the Institutional Structure of the Economy on Income Inequality of Households: Results of a Cross-National Study - M. L. Dorofeev (Финансы: теория и практика, 2022)
Institutional quality and effectiveness of government institutions are important factors for sustainable and dynamic economic growth. These factors can have a significant impact on the dynamics of economic inequality and poverty in a country. The number of publications on this topic began to increase about 20–30 years ago. Scientists have been researching whether the government is able to influence the problem of economic inequality, which is growing since the 1980s, and on what factors it depends.This topic remains relevant today, as all the necessary answers have not been received yet.The purpose of this research article is to clarify the relationships between the institutional structure quality of an economy and the income inequality of households.The article uses such methods as analysis and synthesis, systematization, classification, and categorization of information; classical correlation analysis, as well as the method of analysis of qualitative pairwise correlation. The study highlights that there is high dependence between the analyzed variables in some countries if we look at them in separately. This dependency can take on both negative and positive values. At the same time, analyzing the full sample of countries, as well as in quartile groups classified by the level of income inequality, we did not reveal any pattern or special sign by which the dependence between the studied variables becomes more pronounced and distant from zero. The study shows that the correlation value between the variables is just below zero over the Pearson correlation coefficient. More unambiguous results were obtained when the list of countries was filtered by the indicator of the inequality transparency index. When analyzing this particular portion of our sample of countries, we obtained results with moderately negative dependence between the study variables.We concluded that for developed countries with an effective government and relatively low levels of income inequality, the decline in the quality of the institutional structure of the economy on average will be accompanied by an increase in income inequality and vice versa.